The mediating role of place attachment on the perceived value & destination loyalty relationship: A conceptual model - Nur Izzati, Ab Ghani; Muhamad Nasyat, Muhamad Nasir (2021)
Terengganu is one of the states in Malaysia that possesses the advantages of having beautiful islands and delicious local foods Despite having these competitive advantages. recent statistics reported that Terengganu is among the least states in Malaysia receiving local tourist arrivals. Therefore. it is important to improve destination loyalty to increase domestic tourist arrivals to Terengganu. Hence, the study's main objective is to develop a new conceptual model comprising the relationship of perceived value, place attachment. and destination loyalty among domestic tourists In Terengganu. Most importantly. this study proposes to examine the mediating effect of place attachment on the relationship between perceived value and destination loyalty because limited number of studies have tested this mediating effect. Thus, the study introduces a new conceptual model to researchers and practitioners to better understand the concept of perceived value and place attachment to enhance domestic touring' loyalty to Terengganu.